Rowers' on-water power output is commonly underestimated - Lintmeijer, L. L.; Hofmijster, M. J.; Beek, P. J.; Schulte Fischedick, G. A.; Zijlstra, P. J.; Soest, A. J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: In rowing, mechanical power output is a key parameter for biophysical analyses and monitoring of performance and should therefore be measured accurately [1,2]. It is common practice to estimate a rower`s on-water power output as the time average of the dot product of the moment of the handle force relative to the oar pin (MFh,r) and the oar angular velocity ( o) [3,4]. In a theoretical analysis we have shown that this measure differs from the true power output (Prower) by an amount that equals the mean of the rower`s mass (Mr) multiplied by the rower`s center of mass acceleration (Arcom) and the velocity of the boat (Vb) (Presidual). The purpose of this study was to quantify Presidual for different rowers under different rowing conditions. Methods: Nine rowers participated in an on-water experiment consisting of 7 trials in a single scull. Stroke rate, technique and forces applied to the oar were varied between trials. Inertial sensors (Xsens MVN motion capture suit; 60Hz), a GPS (LOCOSYS, Taiwan; 10Hz) and a pre-calibrated conventional digital scale obtain Arcom, Vb and Mr. Forces applied to the oar and oar angle were determined using instrumented oarlocks (Peach Innovations, UK; 100Hz). The average ratio of Presidual to Prower per trial was calculated as a measure of the difference between true power output and power output estimated while using the common proxy. Results: On average, the ratio of Presidual to true power output was 0.123 with only small variations between rowers and rowing conditions (SD = 0.011). A multilevel analysis revealed an effect of stroke rate: an increase in stroke rate from 18 to 32 strokes per minute resulted in an increase of the ratio of Presidual to true power output from 0.120 to 0.133 (p<.001). Discussion: The results of this study indicate that a rower`s mechanical power output is underestimated by 12.3% on average when calculated according to the common proxy. In order to accurately analyze and monitor rowing performance, a correction of the determination of rowers` on-water power output is, therefore, required.